What do petrochemical workers, healthcare workers, and truck drivers have in common? Evaluation of sleep and alertness in Brazilian shiftworkers - Frida Marina Fischer (Cadernos de Saúde Pública)
The article reports briefly on some effects of shiftwork and the work environment on health and wellbeing of shiftworkers. Studies of Brazilian shiftworkers (healthcare workers, petrochemical workers, and truck drivers) are described. A similar methodology was used to evaluate sleep and alertness in all these studies. The evaluation of sleep duration and quality and alertness showed similar results in the three studies. Although the workers were in different work settings, performing different jobs, the results are similar: daytime sleep is reduced and perceived as having worse quality than nighttime sleep; alertness decreases as the night work progresses. The study highlights the importance of shiftwork schedules' features and work organization for workers' health, wellbeing, and safety.